Navigating urbanization implications: effects of land expropriation on farmers’ livelihoods in Addis Ababa, Ethiopia - Ayenachew, Yeshitla Agonafir; Abebe, Birhanu Girma (Frontiers in Sustainable Cities, 2024)
Land expropriation has become a common practice in Ethiopia, related to the growing demand for land due to rapid urbanization and economic development. The Addis Ababa city administration extensively applies expropriation as a strategy to acquire and allocate land for various public development projects, including low-cost housing, real estate, industrial parks, and infrastructure initiatives. This paper investigates the effect of land expropriation on the livelihoods of farmers who are expropriated in the peripheries of Addis Ababa, Ethiopia. The study employed a mixed methods approach to data collection, namely, household surveys, key informant interviews, field visits, and document reviews. The study used 349 sample expropriated farmer household heads drawn from four purposively selected sub-cities using a systematic random sampling technique. The findings reveal that there was a lack of transparency and consultation during the expropriation process, leaving affected farmers dissatisfied. There was an inadequacy of compensation and insufficient resettlement support provided by the city administration. The findings reveal that the expropriation has significant adverse effects on the livelihoods of the expropriated farmers like income losses, unemployment, and reduced agricultural production. The living conditions of most farmers have deteriorated after the expropriation. To address these issues, the study recommends enhanced procedural clarity, meaningful participation, and consultation with affected farmers during expropriation processes. The city administration should provide resettlement support to help affected farmers shift into new livelihoods like access to housing, employment opportunities, access to credit, and social services.